Çinko Ve Nikel Kaplanmış Düşük Karbonlu Çelik Plaka Ve Vidaların Korozyon Davranışının İncelenmesi - Tuna, Nedret (Fen Bilimleri Enstitüsü, 2013)
Çinko ve nikel kaplamalı malzemelerin korozyon davranışı ile ilgili bilgi sahibi olmak için kullanılan yöntemler oldukça uzun süreler gerektirmekte ve objektif veriler elde edilememektedir. Elektrokimyasal Empedans Spektroskopisi (EIS) yöntemi, korozyonu sayısallaştırarak mevcut yöntemlerden farklı olarak test sonuçlarının objektif bir şekilde değerlendirilebilmesine olanak sağlamaktadır. Ayrıca farklı çalışma ortamlarında ve farklı geometriye sahip parçalarda da kaplama performansı test edilebilmektedir. Bu tez çalışması kapsamında, yaklaşık 25 cm2 boyutlarında DC03 kalite düşük karbonlu çelik plakalar üzerine farklı kaplama sürelerinde elektrolitik çinko ve nikel kaplamalar yapılarak, bunların tuzlu su sisi testi ile polarizasyon dirençleri arasında bir ilişki kurulmaya çalışılmıştır. Bu bağlamda, kaplama firmalarından çinko ve nikel kaplamalar için elektrolitik kaplama öncesi kullanılan temizleme çözeltileri ve proses banyoları temin edilmiş, laboratuvar ortamında bu proses banyoları kullanılarak çelik plakalar üzerine farklı kalınlıklarda çinko ve nikel kaplamalar gerçekleştirilmiştir. İlk seri kaplamaların kalınlıkları Fischerscope XDL kalınlık ölçüm cihazı kullanılarak tahribatsız olarak ölçülmüştür. İkinci seri kaplamalarda ise mevcut kaplama kalınlıkları, numuneden kesit alınıp optik mikroskopta incelenerek tespit edilmiştir. Tuzlu su sisi testleri ASTM B117 standardına uygun olarak Weiss SC450 kabin kullanılarak yapılmıştır. I.seri plakalarda yapılan tuzlu su sisi testlerinde numuneler 30dk aralıklarla korozyon açısından kontrol edilmiştir. II.seri plakalarda korozyon verisini sayısallaştırmak amacıyla şablonlar oluşturulmuş, çinko kaplamalı plakalar için beyaz pas görülen kare adedi ile nikel kaplamalar için birim alandaki oyuk miktarı olarak değerlendirilmiştir. Çinko kaplamalı vidalar için kaplamanın en ince bölgesinin tayini için kullanılan bakır sülfat testi yapılarak korozyon dayanımı hakkında öngörülerde bulunulmuş ve bu doğrultuda EIS testleri ile doğrulanması amaçlanmıştır. Nikel kaplamalı plakalarda ve taban malzemede yüzey pürüzlülüğü ölçülmüş, kaplama kalınlığı ve polarizasyon direnci ile ilişkilendirilmiştir. Nikel kaplamalı vidalar için porozitenin tayinine yönelik modifiye sıcak su testi yapılmış, testten geçen ve kalan vidalara test öncesi ve sonrası EIS testi yapılarak, porozite tayini ile korozyon ömrü arasında ilişki kurulmaya çalışılmıştır. EIS testi atmosfere açık ortamda ve oda sıcaklığında olacak şekilde %3,5 NaCl çözeltisi içerisinde gerçekleştirilmiştir. Çalışma sonunda, çinko kaplanmış plakaların tuzlu su sisi testinde görülen hata miktarı ile polarizasyon dirençleri arasında ömür tayinine yönelik ilişki kurulabilmiştir. EIS testi ile mevcut korozyon testlerinin korelasyonu yapılarak ikinci aşama olan çinko kaplamalı vidalar için kaplama kalınlığı hakkında bilgi vermekte olan testler uygulanmıştır. Bu testlerden geçen ve kalan vidalar için EIS testleri uygulanarak bakır sülfat testinin çinko kaplamalı vidalarda hızlı bir ön değerlendirme olarak kullanılabileceği görülmüştür. Nikel kaplanmış plakalarda 6 saatlik test süresinin literatürde de karşılaşıldığı üzere kaplama üzerinde pasif film oluşmasından dolayı yetersiz kaldığı görülmüş, bundan dolayı test süresinin 30 saate kadar uzatılması gerektiği sonucuna varılmıştır. Yüzey pürüzlülüğünün nikel kaplamalar için korozyon ömrü bakımından çok etkili bir parametre olduğu görülmüş, kaplama kalınlığı ile açıklanamayan polarizasyon direnci değişimlerinde yüzey pürüzlülüğünün etkili olduğu anlaşılmıştır. Nikel kaplamalı vidalarla gerçekleştirilen modifiye sıcak su testi ile EIS ölçümleri sonucunda porozitenin korozyon ömrüne etkisi görülmüştür. Her iki kaplama için de banyo çözeltisindeki metal miktarının kaplamanın kalınlığına olan etkisi, banyo çözeltisine çinko veya nikel takviyesi yapılmasından önce ve sonra alınan banyo çözeltileriyle yapılmış olan kaplamalar aracılığıyla anlaşılmıştır.

The use of metal has increased day by day and at the same time the loss of materials and manpower caused by metal corrosion has reached serious proportions. The metallic coating was applied to solve this problem because of its easy practice and success in improvement the service life. Metallic coatings became an important and necessary method to improve surface properties of the base metals, which exhibit limited corrosion, wear and oxidation resistances. Zinc and nickel coatings are used succesfully for many years for protection of ferrous alloys against corrosion attack. In addition to the coatings, the passivation process draw the attention for a decorative appearance, while providing enhancement in the corrosion resistance. There are limited number of studies about the prediction of service life of protective coatings. In these studies, EIS measurements have performed in different operating environments in order to determinate the lifetime of the coatings’ and to establish a relationship between the other corrosion test results. Studies in this area showed that when the polarization resistance of coatings drop below 107 , the corrosion resistance severely damaged. Hence, in this thesis the relationship between polarization resistance values obtained from EIS measurements and salt spray test values were correlated. Generation of defects in salt spray test was accompanied by a reduction in polarization resistance. The methods for determination of corrosion behavior of the zinc and nickel coated materials need very long time periods and may not present an objective data. In contrast to the existing methods, Electrochemical Impedance Spectroscopy (EIS) method allows the evaluation of test results objectively by digitizing progress. In addition, components that have different geometry can be tested in different operating environments. In this thesis,electrolytic zinc and nickel coatings applied on DC 03 quality low-carbon steel sheets in different coating times and tried to establish a relationship between their salt spray test and the polarization resistance. The cleaning solutions that are used before electroplating process were also obtain from the relevant industrial companies. Zinc coating was performed for 13,5 and 15 min. Nickel coating was performed for 8, 10, 13, 15 and 18 min after 1-min copper plating. The thickness of the coatings were measured by Fischerscope XDL thickness measurind device and optical microscope. Electrolytic bath solutions were obtained from the relevant coating companies. Since the zinc and/or nickel contents of the electrolytes were reduced as they have been used in the coating operations, metal ion concentrations of the electrolytes were adjusted at certain intervals by adding zinc and/or nickel. Therefore in the present study with or without addition of these metals were utilized in order to analyze the effect of metal ion concentration of the electrolytes. EIS test was applied according to the principle of three-electrodes. The saturated calomel electrode was used as the reference electrode, the graphite rod was used as the counter electrode and plates coated with zinc or nickel were used as the anode. Working life of coatings without progress of corrosion correlated with estimated porosity. EIS test was performed at room temperature in 3,5% NaCl solution. EIS measurements were performed by using the Voltmaster 4 program with the Voltalab 40 PGZ 301 device. Measurements were performed at the frequency range of 100kHz-10mHz and the EIS graphics were obtained in the Bode form. Salt spray tests were made by using Weiss SC450 cabin in accordance with ASTM B117 standard. In order to quantify the performances of coatings, coating surfaces paterned in forty squares.The number of white rust frame was evaluated for zinc-coated plates and amount of pit was counted for nickel -coated plates. The ratio of the defects generated in salt spray test on the zinc coatings were correlated with the polarization resistance to estimate working life. Number of defects in salt spray test have been identified in response to a significant decrease in the value of polarization resistance. The copper sulfate test were conducted to correlate the results with EIS tests used to find the thinnest spot of the zinc coating screws. The copper sulfate solution was prepared by dissolving approximately 36 parts of commercial cupric sulfate crystals (CuSO4.5H2O) by weight in 100 parts of distilled water. The prepared solution then heated to add 0.8 g/L cupric oxide (CuO). Specimens were immersed in the copper sulfate solution which maintained at a temperature of 16 to 20˚C. Specimens were remained in a fixed position in the solution for exactly 1 min. After each 1-min immersion, specimens were washed in the rinse water to remove any copper deposit that might be present on zinc coatings. This process was repeated until the end point has been reached. Modified hot water test applied to the nickel-coated screws to determine the porosities present in the coatings. The screws immersed in 90˚C salty distilled water (~ 0.5 % NaCl solution) for two hours. Two-hours test period started when the water temperature was reached the temperature at 90˚C. At the end of the test period, screws was removed from the hot water and was dried with the air. EIS test applied to screws after the hot water test. Following results were obtained from the experiments conducted in the present study. • In order to make correlation between salty water and impedance test results for corrosion life of coatings, the results of the corrosion test should be quantified. In this respect, present study showed that number of white rust per unit area and number of pits per unit area should be considered for zinc and nickel coatings respectively. • The EIS test conducted immidiately after immersing the sample in solution did not give sufficient information about corrosion resistance of the coatings. Therefore EIS graphics should be obtained after holding the samples in the solutions for certain time period. • For the zinc-coated plates increase in number of defects after salt spray tests accompanied by a reduction in polarization resistance. These results indicated that a correlation can be established between salt spray and EIS tests for corrosion life of zinc coatings. • For the nickel coated plates, holding time in salty water shorter time 5-hour leaded corrosion, whose progress was not identified clearly by EIS tests. In the literature it has been reported that corrosion resistance of nickel coatings were poor at the beginning of the tests and tended to increase with holding time especially after 30 min to 4 hours. Longer holding times companied by a reduction in corrosion resistance. Since similar results have been obtained in the present study, the correlation between EIS and salt spray test have been made after holding the samples in salty water for 30 hours. • If EIS tests for nickel-coated plates continue until the breaking point of polarization resistance, the effect of the passive layer on the coating can be avoided. Polarization resistance may provide information about the corrosion mechanism of the samples with complex geometry, other than flat plates. Determined by the polarization resistance value will be accepted and with movement of the polarization resistance at time zero, corrosion life or the sample can be determined. • For the nickel coated plates, the increase of copper flash and nickel thickness cause increase of polarization resistance. Higher surface roghness values leaded reduction of polarization resistance. • EIS tests which conducted on the zinc-coated screws, after copper sulfate test, revealed the limit value of polarization resistance. Zinc-coated samples should exhibit polarization resistance value higher than 4,2 E8 Ω for required corrosion performance. If the number of EIS tests of zinc-coated screws increase at time zero, a database can be prepared. The database of polarization resistance values may give information about coatings’ life prediction. • Modified hot water test has been developed for pass/fail criteria of nickel coated screws. The limit polarization resistance has been determined as 4,5 E8 Ω for nickel-coated samples. • With increasing the number of tests (modified hot water tests for nickel coatings and copper sulphate tests for zinc coatings) of screws by comparing with EIS test results may provide more information about the complex geometry brought dispersion.
Investigation Of Corrosion Behavior Of Zinc And Nickel Coated Low Carbon Steel Plates And Screws
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2013
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2013
Keywords: çinko oksit; çinko; nikel; nikel kaplama; galvaniz; elektrolit çözeltiler; elektrolitik; paslanmaz çelik; zinc oxide; zinc; nickel; nickel plating; galvanization; electroyte solutions; electrolytic; stainless steel